New medical treatments for lower urinary tract symptoms due to benign prostatic hyperplasia and future perspectives. Issue 1 (December 2016) - Albisinni, Simone; Biaou, Ibrahim; Marcelis, Quentin; Aoun, Fouad; De Nunzio, Cosimo; Roumeguère, Thierry
Abstract Background Lower Urinary Tract Symptoms (LUTS) in men are a common clinical problem in urology and have been historically strictly linked to benign prostatic hyperplasia (BPH), which may lead to bladder outlet obstruction (BOO). New molecules have been approved and have entered the urologists' armamentarium, targeting new signaling pathways and tackling specific aspects of LUTS. Objective of this review is to summarize the evidence regarding the new medical therapies currently available for male non-neurogenic LUTS, including superselective α1-antagonists, PDE-5 inhibitors, anticholinergic drugs and intraprostatic onabotulinum toxin injections. Methods The National Library of Medicine Database was searched for relevant articles published between January 2006 and December 2015, including the combination of "BPH", "LUTS", "medical" and "new". Each article's title, abstract and text were reviewed for their appropriateness and their relevance. One hundred forty eight articles were reviewed. Results Of the 148 articles reviewed, 92 were excluded. Silodosin may be considered a valid alternative to non-selective α1-antagonists, especially in the older patients where blood pressure alterations may determine major clinical problems and ejaculatory alterations may be not truly bothersome. Tadalafil 5 mg causes a significant decrease of IPSS score with an amelioration of patients' QoL, although with no significant increase in Qmax . Antimuscarinic drugs are effective on storage symptoms but should be used with caution in patients with elevated post-void residual. Intraprostatic injections of botulinum toxin are well-tolerated and effective, with a low rate of adverse events; however profound ameliorations were seen also in the sham arms of RCTs evaluating intraprostatic injections. Conclusion New drugs have been approved in the last years in the medical treatment of BPH-related LUTS. Practicing urologists should be familair with their pharmacodynamics and pharmacokinetics.